PENGARUH PENERAPAN TEKNIK BISNIS BERESIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 SUTERA - Irayuni, Winda; Rahmi, Rahmi; febriana, Rina (Pendidikan Matematika, 2014)
ABSTRACTThis research is motivated by the students understanding of mathematical concepts are still low. This study aims to determine whether students understanding of mathematical concepts by applying Bisnis Beresiko Technique better than students understanding of mathematical concepts with the application of conventional learning. This type of research is experimental, the research design random design to subject. The population in this research is the students in grade VIII SMPN I Sutera. Sampling was done by random sampling, that is similar to the decision classes VIII.3 as eksperimental and VIII.1 as control. The instruments that is used in this essay test. Results of data analysis that the two classes are normally distributed and homogeneous samples and t test results obtained P-value=0,02 is less than Î±=0,05, so that hypothesis is approved. It can be concluded that the students understanding of mathematical concepts by applying Bisnis Beresiko Technique grade better than students understanding of mathematical concepts by applying conventional learning models VIII grade SMPN 1 Sutera.